Deprescribing attitudes and predictors among older adults attending geriatric clinics in Kuwait. - Hesah Alshammari; Eman Al-Saeed; Zamzam Ahmed; Zoe Aslanpour (PLoS ONE)
Deprescribing is defined as the reduction of medications to improve patient care. For effective deprescribing regular evaluation of medication adjustment regimens is required as it is documented to be an effective method to reduce polypharmacy and potentially inappropriate medications while improving patient well-being. Several factors, including patient-related aspects, influence the deprescribing process. Among these factors, patient willingness plays a pivotal role, making it essential to better understand their perspectives and attitudes towards medication use and deprescribing to successfully implement and maintain a deprescribing approach. We investigated the attitudes of older patients attending geriatric clinics in Kuwait toward deprescribing and identified predictors that influence their willingness to undergo this process. We enrolled patients aged ≥65 years who were attending geriatric clinics in primary care settings in Kuwait. These participants completed the revised Arabic version of the Patients' Attitudes Towards Deprescribing (rPATD) questionnaire. The questionnaire was designed to assess the participants' willingness to participate actively in medication decision-making and their inclination toward discontinuing certain medicines. Descriptive statistics was applied to gain insight into the characteristics of the participants and their responses to the rPATD questionnaire. Binary logistic regression identified predictors influencing the desire to deprescribe among participants. The study included 535 participants, out of which 388 were analyzed, with 233 (43.6%) being women. The majority, 77% (n = 412), were aged between 65 and 74 years. Out of the total, 205 patients (38.4%) had one to two medical conditions and were prescribed between one and five medications. The participants showed a high willingness to deprescribe, and this willingness was inversely associated with sex (p = 0.15), age (p = 0.15), and polypharmacy (p = 0.044). Many older patients visiting geriatric clinics in primary care settings in Kuwait were receptive to the concept of deprescribing medications, particularly if advised by their doctor. Nevertheless, it was observed that male patients, individuals on more than 5 medications, and older age groups showed lower willingness to deprescribe.